COMMUNITY CHARACTERISTICS AND CONDITIONS OF SANITATION FACILITIES IN THE MUSI RIVERSIDE SETTLEMENT KELURAHAN SATU ULU PALEMBANG IN 2022 - Priyadi; Pitri Noviadi; Serly Wiranda; Sinthia Khodijah Marpaung; Tri Ariska Mulia (Perhimpunan Ahli Epidemiologi Indonesia, 2022)
Background: According to data from the Working Group on Development, Housing, Settlements, Water and Sanitation (POKJA PPAS) in 2021, the access to decent sanitation in South Sumatra is still below the National achievement of 77.2%. In facts, the condition of settlements on the banks of the river has gone out of control cause of unqualified basic sanitation. Methods: The type of research used is a descriptive survey. This research was conducted in March-May 2022. The population of this study were all 315 households in Kelurahan Satu Ulu located on the banks of the Musi river. The sample of this study was communities on the banks of the Musi River, Kelurahan 1 Ulu totaling 76 respondents. The sampling technique is Probability Sampling with the Proportionate Stratified Random Sampling method. Results: Of the 76 respondents, high education 47 (61.8%), low education 29 (38.2%), formal livelihoods 5 (66%), non-formal livelihoods 71 (93.4%) low income 41 (53.9%), medium income 35 (46.1%), clean water qualified 33 (43.4%), clean water are not eligible 43 (56.6%) family latrine are eligible 41 (53.9%), family latrine are not eligible 35 (46.1%), wastewater sewers are eligible 27 (35.5%), wastewater sewers are unqualified 49 (64.5%) garbage reservoirs are eligible 40 (52.6%), waste shelters are not eligible 36 (47.4%). Conclusion: Clean water, family latrine, wastewater sewers are in the unqualified category while garbage shelters are included in the eligible category.